2009
DOI: 10.1371/journal.pone.0008017
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterial MsDps2 Protein Is a Nucleoid-Forming DNA Binding Protein Regulated by Sigma Factors σA and σB

Abstract: The Dps (DNA-binding protein from starved cells) proteins from Mycobacterium smegmatis MsDps1 and MsDps2 are both DNA-binding proteins with some differences. While MsDps1 has two oligomeric states, with one of them responsible for DNA binding, MsDps2 has only one DNA-binding oligomeric state. Both the proteins however, show iron-binding activity. The MsDps1 protein has been shown previously to be induced under conditions of starvation and osmotic stress and is regulated by the extra cellular sigma factors σH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…Due to the increase in the number of fully sequenced microbial genomes, many Dps homologs were found, and their structures and functions were clarified [21,22]. It is common amongst bacteria to have more than one Dps gene per genome [23]. A number of studies have demonstrated the Dps expression control at the transcription level [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increase in the number of fully sequenced microbial genomes, many Dps homologs were found, and their structures and functions were clarified [21,22]. It is common amongst bacteria to have more than one Dps gene per genome [23]. A number of studies have demonstrated the Dps expression control at the transcription level [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Here we used pure proteins and added plasmid DNA. We reported earlier, that MsDps2 is purified from cells in DNA bound form [20]. Hence we used only purified Dps2 protein, and, on the other hand, we added plasmid pGEM-7Zf(+) to pure Dps1 protein to generate toroids (Figure 5D and 5E respectively).…”
Section: Resultsmentioning
confidence: 99%
“…We know that the transcription of MsDps2 is regulated by σ B , which is analogous to σ s in E.coli [20]. The rpos gene, that is sensitive to post-transcriptional modification, regulates the sigma factor σ s [7], [43].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing numbers of completely sequenced microbial genomes, multiple dps homologs within the same species are now being identified and their structures and functions elucidated [24], [25], [26]. Having more than one dps gene per genome is common amongst bacteria [27]. However, for many genera, variation in the number of dps per genome amongst closely related species is yet to be satisfactorily explained.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, more intricate studies are now characterizing the control of dps at the transcriptional level [27], [30] and, not only is there evidence for multiple sigma factor complexes contributing to the transcription of dps [30], [31] but, it also appears that expression of these genes may be driven by suites of different sigma factors e.g. msdps1 [31] and msdps2 [27]. Together, this suggests that the evolutionary history of dps in many genera contains duplications, losses and possible lateral acquisitions.…”
Section: Introductionmentioning
confidence: 99%